Functional traits and habitat use: Investigating community assembly in a montane community (Carabidae: Nebria) - Jillian K. Schat; David H. Kavanaugh; Jacki Whisenant; Genevieve Anderegg; Huijun Xiao; Sean D. Schoville (Ecosphere)
Abstract The processes that influence community assembly, such as competition for resources and environmental filtering, are often scale dependent and vary across ecotones. Trait‐based ecology provides a useful framework for testing which ecological processes most strongly influence local community composition, especially across environmental gradients where species diversity varies. Where environmental filtering dominates, species distributions are expected to be defined by strong turnover along environmental gradients, with more similar species occupying more similar habitats. Where interspecific competition dominates, species are expected to diverge in relative abundance and resource utilization at sites, so species can co‐occur. Here, we integrate measurements of functional traits, microhabitat usage, isotopic composition (δ15N and δ13C), and abundance to test the importance of environmental filtering and resource/habitat partitioning in shaping a montane ground beetle species assemblage (Carabidae: Nebriini: Nebria) in the isolated, volcanic peaks of the northern Cascades Range, USA. Across species of Nebria, body size, pronotal shape, temperature preference, and isotopic enrichment varied across habitats ([gravel, rocks 10 cm–50 cm in diameter], large rocks [>50 cm in diameter], vegetation‐covered rocks, and alpine [snowfields and talus]), and habitat/microhabitat features were reliable predictors of species presence. Resource consumption among mid‐elevation species on Mt. Rainier—the peak with the greatest species diversity—is highly overlapping. Species turnover and nestedness varied significantly across habitat gradients and peaks throughout this region and varied nearly significantly across sites. Across habitat types and sites, more similar species are more likely to coexist. These results suggest that environmental filtering is the primary process structuring this species assemblage, although we find detailed evidence for microhabitat niche partitioning among species of Nebria at the site scale.